2021
DOI: 10.3390/hydrogen2020012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hydrogen in Inorganic Materials and Coatings: A Critical Review

Abstract: The currently used bulk analysis and depth profiling methods for hydrogen in inorganic materials and inorganic coatings are reviewed. Bulk analysis of hydrogen is based on fusion of macroscopic samples in an inert gas and the detection of the thereby released gaseous H2 using inert gas fusion (IGF) and thermal desorption spectroscopy (TDS). They offer excellent accuracy and sensitivity. Depth profiling methods involve glow discharge optical emission spectroscopy and mass spectrometry (GDOES and GDMS), laser-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 104 publications
0
12
0
Order By: Relevance
“…The spatial resolution of the Raman mapping typically ranges from 0.5-6 µm with a 532 nm laser, depending on the objective lens [12]. These spatial resolutions are far better than those of bulk testing methods proposed by Weiss [4]. Therefore, this study showed great progress in probing local hydride content at a microscopic scale, although neutron imaging could still be superior in terms of scan volume and accuracy [5].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The spatial resolution of the Raman mapping typically ranges from 0.5-6 µm with a 532 nm laser, depending on the objective lens [12]. These spatial resolutions are far better than those of bulk testing methods proposed by Weiss [4]. Therefore, this study showed great progress in probing local hydride content at a microscopic scale, although neutron imaging could still be superior in terms of scan volume and accuracy [5].…”
Section: Discussionmentioning
confidence: 90%
“…Bulk H content is typically measured by the weight gain of sample before and after hydriding [2], which results in a nominal composition, assuming a uniform microstructure. The other methods for the bulk analysis of H include inert gas fusion, thermal desorption spectroscopy, glow discharge optical emission spectroscopy and mass spectrometry, laser-induced breakdown spectroscopy, secondary ion mass spectrometry, nuclear reaction analysis, and elastic recoil detection analysis [4]. Despite various options for the bulk analysis of H, the local H analysis of bulk specimen at a microscale has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…This requires a prescribed relation of volume to surface geometry of the individual material pieces of the PTS, and a prescribed cleaning procedure to be applied immediately prior to weighing, such that the well-defined state is reached for which the certified value applies. Very sophisticated methods, such as photon activation analysis and then removing surface oxygen, can be used to reliably distinguish between oxygen on the surface and in the bulk of the material [20][21][22][23]. For the measurement of "gaseous" components in the candidate material, only direct solid sampling methods can be used, such as glow discharge mass spectrometry (GDMS), carrier gas hot extraction (CGHE), or the combustion method for other non-metallic impurities.…”
Section: Classical Primary Methods (Cpm) and Primary Difference Metho...mentioning
confidence: 99%
“…Despite some of these most common and frequently used techniques having a blind spot for hydrogen, many other techniques are capable of directly measuring and quantifying hydrogen in materials. Excellent reviews have published that contrast a variety of these hydrogen measurement techniques [52][53][54]. Table 3 provides a list of available techniques used for measuring hydrogen in fusion and fission relevant materials.…”
Section: Techniques For Measuring Hydrogen Retentionmentioning
confidence: 99%
“…The energy spectrum of the emitting alpha particles is measured and used to determine the D inventory in the sample [57]. The reaction yield is proportional to the flux of incident 3 He ions and the cross section [52].…”
Section: Techniques For Measuring Hydrogen Retentionmentioning
confidence: 99%